Load-carrying capacity of short implants in edentulous posterior maxilla: A finite element study - Demenko, Vladislav; Linetskiy, Igor; Linetska, Larysa; Yefremov, Oleg (Medical engineering & physics, 2019)
Dental implant dimensions, and bone quality and quantity play a key role in early osseointegration and long-term prognosis in posterior edentulous maxilla. Treatment with short implants, preferably in a bicortical manner, is an accepted modality; however, short implants have limitations leading to increased stress concentrations in alveolar bone, potential overload and implant failure. Implant models of 3.3, 4.1, 4.8 and 5.4 mm diameter and 4.5, 5.5, 6.5, 7.5 and 8.5 mm length were placed in posterior maxilla 3-D models with corresponding residual bone heights. Bone-implant assemblies were analyzed in finite element software ANSYS 15. All materials were assumed to be linearly elastic and isotropic. 118.2 N oblique loading was applied to investigate stress distributions in bone tissues. The concept of ultimate functional load (UFL) was selected as a criterion to compare load-carrying capacity of implants and to evaluate the influence of available bone height and implant dimensions on load-carrying capacity. For all implants, UFL was calculated by limiting von Mises stresses in cortical or cancellous bone with bone strength (100 MPa for cortical and 2 MPa for cancellous bone). Implant load-carrying capacity depends on diameter and available bone height. Wide implants have higher load-carrying capacity than narrow implants. Short implants with proper diameter and length avoid bone overstress, even in Type IV bone.
Keywords: Humans; Materials Testing; Finite Element Analysis; zubní implantáty; Osseointegration; analýza metodou konečných prvků; testování materiálů; osteointegrace; Dental Implants; Dental Prosthesis Design; maxila; zatížení muskuloskeletálního systému; Maxilla; lidé; Weight-Bearing; zubní protéza - design